The Evaluation of Silicon Oil Evacuation Procedure In Cipto Mangunkusumo Hospital Indonesia - Triwijayanti Triwijayanti; Ari Djatikusumo; Andi Arus Victor; Elvioza Elvioza; Gitalisa Andayani Adriono; Anggun Rama Yudantha; Mario Marbungaran Hutapea (Indonesian Vitreoretinal Society, 2019)
Background: Injection of Silicon oil is a standard procedure for vitreous replacement in vitrectomy procedure for retinal detachment cases. It acts as a great tamponading agent for reattachment of retinal breaks or retinal detachment. Despite its minor side effect, silicon oil could cause several complications such as cataract, endothelia decompensation, increased intraocular pressure, and secondary glaucoma. Thus needed to be evacuated after the retinal reattachment is stabilized. Following evacuation procedure, visual acuity are known to be significantly improved. However, some cases shows decreased of visual acuity due to retinal redetachment, optic nerve damage due to secondary glaucoma, hypotonym vitreous hemorrhage, expulsive hemorrhage, and cornea abnormality. Methods: A retrospective descriptive study of retinal detachment patients underwent silicon oil evacuation procedure in Cipto Mangunkusumo Hospital, Indonesia from September 2017 until Januari 2018. Results: There were seventy seven cases of retinal detachment undergoes silicon oil evacuation within period of September 2017-Januari 2018. There were improvement of visual acuity (greater than 6/60) after one month of silicon oil evacuation. Anatomical retinal reattachment was successfully observed in 91% patient. The most occuring complication after silicon oil evacuation includes secondary glaucoma and retinal redetachment. Conclusion: Silicon oil evacuation is a standard procedure following a vitrectomy in retinal detachment cases. The evacuation procedure yields in positive benefit for patient in term of visual acuity and anatomical structure.